2010
DOI: 10.1164/rccm.200908-1297oc
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response-1 Worsens Ventilator-induced Lung Injury by Up-Regulating Prostanoid Synthesis

Abstract: This is the first demonstration of a mechanism whereby expression of a novel gene (Egr1) can contribute to VILI via a prostanoid-mediated pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 60 publications
2
25
1
Order By: Relevance
“…Pressure-based VILI experiments yielded similar results (data not shown). VILI has been shown to be attenuated in Egr12/2 KO mice (22). Our microarray analysis demonstrated that expression of Egr1 was decreased 14.0-fold in C18 KO mice (Table E3), and this finding was confirmed by qRT-PCR, which showed a 22.5-fold decrease in lungs of C18 KO mice ( Figure 7B).…”
Section: Lower Sensitivity To Ventilatorinduced Lung Injury In C18 Kosupporting
confidence: 59%
See 2 more Smart Citations
“…Pressure-based VILI experiments yielded similar results (data not shown). VILI has been shown to be attenuated in Egr12/2 KO mice (22). Our microarray analysis demonstrated that expression of Egr1 was decreased 14.0-fold in C18 KO mice (Table E3), and this finding was confirmed by qRT-PCR, which showed a 22.5-fold decrease in lungs of C18 KO mice ( Figure 7B).…”
Section: Lower Sensitivity To Ventilatorinduced Lung Injury In C18 Kosupporting
confidence: 59%
“…Microarray and qRT-PCR gene expression analysis revealed a large decrease in expression of the transcription factor Egr-1 in C18 KO lungs. EGR-1 activates expression of the gene encoding prostaglandin E synthase, an enzyme that increases synthesis of prostaglandin E2, which exacerbates inflammation and lung injury by activating pulmonary prostaglandin E receptor subtype 1 (22). Accordingly, Egr-1 KO mice feature significantly lower levels of injury in response to VILI (22), suggesting that lower Egr-1 expression in C18 KO mice is protective.…”
Section: Changes In Expression/localization Of Other Tjs and Tj-assocmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK may increase permeability by promoting apoptosis, oxidant production and activation of myosin-light chain kinase, which activates molecular motor myosin to promote endothelial cytoskeletal contraction and subsequent interendothelial gap formation [12,[41][42][43]. ERK is strongly activated in VILI experiments and has been used as an injury marker in VILI [44,45]. ERK inhibition by a small-molecule inhibitor has been effective in rescuing a mouse model of endotoxin-induced lung injury [46] and mixed models of VILI and bleomycin or hyperoxia [12,47].…”
mentioning
confidence: 99%
“…Therefore, targeting this chemokine could be an effective approach to avoid VILI in this context. Other authors have used genomic studies to identify therapeutic targets, resulting in attenuation of VILI (26). However, it must .…”
Section: Sh3bgrl3mentioning
confidence: 99%